Childhood Risk Factors for Self-Reported Versus Official Life-Course-Persistent, Adolescence-Limited, and Late-Onset Offending - Zara, Georgia (Criminal justice and behavior, 2020)
There has been no prior research comparing risk factors for categories of convicted individuals (C-types: life-course-persistent; adolescence-limited; late-onset) compared with the corresponding categories of individuals who self-reported offending (SR-types). This article examines the extent to which these convicted and self-reported categories of individuals overlap, and explores childhood risk factors that predict categories of C-types and SR-types. Criminal career information about individuals involved in the Cambridge Study in Delinquent Development (CSDD) is used; 25 childhood factors were analyzed. C-types and SR-types were more problematic than both official and SR nonoffenders. Life-course persisters, adolescence-limited offenders, and nonoffenders overlapped in official records and self-reports, but late-onset offenders did not. C-types were significantly similar to SR-types in childhood risk factors; only a few differences were found. The differences between C-types and SR-types might be better conceptualized as quantitative rather than qualitative. Implications for prevention and intervention are discussed.